AERODYNAMIC SURFACE ROUGHNESS LENGTH OFBAGHDAD CITY - Al-Jiboori, Monim H; Al-Draji, Aqeel G (Al-Nahrain Journal of Science, 2010)
A field study carried out to calculate the displacement height, Zd, and roughness length, Z0, for Baghdad city according to several commonly standard criterions. Meteorological equipments such as anemometer, wind vane and thermometer were used to observe wind speed, wind direction and air temperature at two levels of 15 and 20 m. The results show that large variations in Zd and Z0 depend strongly on roughness element height, wind direction and the changes in the upwind fetch. Also, Baghdad city is classified as medium density and urban surface according to the values of measured Zd and Z0.